INTERACTIVE MODEL IN TEACHING READING TO HELP STUDENTS TO UNDERSTAND ENGLISH TEXTS - firmansyah diyata (Ma'soem University, 2021)
To understand English text, students need to have adequate English proficiency background, at least in understanding the grammar and having many vocabularies to understand the text. For those who do not have good proficiency background in such areas, will have difficulties to comprehend every sentence they read on that text. Teachers who face this kind of situation, must have appropriate approach to handle this problem. Interactive model that was applied in this research has an aim to help students to understand the text by understanding the parts of each sentence on the text they read. To find the findings in this research, the writer used mix method of quantitative and qualitative. The method was applied to find out how the interactive model helps students to comprehend the texts they read. There were 25 students who joined this research after they are considered could fulfill its requirements. The research shows that the students who were taught by interactive model developed their understanding of sentence analysis, felt comfortable with the teaching model, but had less development in understanding the text. Based on the findings from this research, it is concluded that the method gives comfortable teaching atmosphere but does not give significant development on students’ reading skill. The method will be able to give more significant result if it is applied to the students who have higher English Proficiency Level, such as in intermediate and advance levels.